The Role of Attitude Toward Learning, Interest in Learning and Digital Literacy in Inventive Thinking Skill: SEM Approach - Eka Ad'hiya; Rodi Edi; Fitrah Amini; Deika Zhillan Fatharani; Diah Kartika Sari; Maefa Eka Haryani (IJECA (International Journal of Education and Curriculum Application), 2025)
The urgency of this research stems from a follow-up to previous research that mapped the level of inventive thinking among chemistry education students at Sriwijaya University, which was found to be at a moderate level. Therefore, it is necessary to conduct further analysis of the factors that influence inventive thinking. This study aims to determine the relationships among Attitude toward Learning, Interest in Learning, and Digital Literacy and Inventive Thinking among Chemistry Education Students at Sriwijaya University. This research is a quantitative, cross-sectional study. Data were collected through a survey. The instrument used was a 59-item Likert-type questionnaire with 4 points on the scale. The questionnaire included 23 items on inventive thinking, 18 on attitude toward learning, 8 on interest in learning, and 10 on digital literacy. The sample for this study consisted of students in the Chemistry Education study program at Sriwijaya University. The research data were analyzed using Structural Equation Modeling (SEM). The results of the measurement model test indicated 26 indicators that were valid and reliable. The results of the structural model evaluation showed no multicollinearity problems, and the model explained 61.1% of the variance in the inventive thinking variable, which was classified as high. The results of the path coefficient significance test showed that only Hypothesis 3 had a t-statistic greater than 1.96 and a p-value less than 0.05, indicating that only digital literacy had a positive and significant effect on inventive thinking. Then the results of this research will have implications for the development of learning designs/learning environments that can support the inventive thinking of chemistry education students by integrating learning with digital literacy.